1990
DOI: 10.1177/0013916590221003
|View full text |Cite
|
Sign up to set email alerts
|

What Makes a Recycler?

Abstract: Knowledge and motivational factors represent important but neglected topics in the study of recycling behavior. This article examines differences in knowledge, motives, and demographic characteristics of people who have the opportunity to recycle voluntarily. Information on these variables was obtained for 197 households in Illinois. The results indicated that recyclers in general were more aware of publicity about recycling and more knowledgeable about materials that were recyclable in the local area and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(120 citation statements)
references
References 12 publications
7
109
0
4
Order By: Relevance
“…The difficulty faced by governments and environmental groups who wish to raise public awareness of the seriousness of global environmental problems, and more importantly, to do something about them is that most global environmental problems such as the destruction of the ozone layer and global warming are regarded as impersonal, indirect and long-term. Vining and Ebro (1990) assert that it is only worthwhile investigating local environmental knowledge as people display difficulties in understanding and assimilating complex, distant problems. Zube (1991) argues for the importance of studying how people perceive and interact with the environment at a local level because it is at this level people function and exist in most meaningful ways.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty faced by governments and environmental groups who wish to raise public awareness of the seriousness of global environmental problems, and more importantly, to do something about them is that most global environmental problems such as the destruction of the ozone layer and global warming are regarded as impersonal, indirect and long-term. Vining and Ebro (1990) assert that it is only worthwhile investigating local environmental knowledge as people display difficulties in understanding and assimilating complex, distant problems. Zube (1991) argues for the importance of studying how people perceive and interact with the environment at a local level because it is at this level people function and exist in most meaningful ways.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the more knowledge a household has about recycle materials and their impact on the natural world, the more likely they will practice it, [26]. S. Oskamp et al, (1991) noted that recycling behaviour may also be affected by lack of knowledge about environmental issues .People who showed higher knowledge and concerns about the environment and recycle, have higher levels of participation with recycling, [34], [27], [6], [31].…”
Section: Knowledgementioning
confidence: 99%
“…not being environmentally-conscious) will have future impacts on society and on quality of life. This has resulted in development of recycling and waste reduction programmes in various communities (Schahn & Holzer, 1990;Vining & Ebreo, 1990). Many people are prepared to commit to improving the environment, but in general, people "actually do very fairly little and know even less" (McGuiness et al, 1977, p. 376).…”
Section: The Nature Of Environmental Behaviourmentioning
confidence: 99%
“…Research has indicated that environmental behaviours are carried out by many different groups of people, motivated by different factors (Corraliza & Berenguer, 2000;Fraj & Martinez, 2006;Kok & Siero, 1985;Oskamp et al, 1991;Van Liere & Dunlap, 1978;Vining & Ebreo, 1990). Studies have investigated the various factors influencing specific environmental behaviours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation